Labor and monopoly capital : the degradation of work in the twentieth century - Braverman, Harry (Monthly Review, 1974)
This widely acclaimed book, first published in 1974, was a classic from its first day in print. Written in a direct, inviting way by Harry Braverman, whose years as an industrial worker gave him rich personal insight into work, Labor and Monopoly Capital overturned the reigning ideologies of academic sociology.